2018
DOI: 10.1186/s12938-018-0591-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the pulmonary hemodynamics and gas exchange with a speed modulated right ventricular assist rotary blood pump: a numerical study

Abstract: Rotary blood pumps (RBPs) are the newest generation of ventricular assist devices. Although their continuous flow characteristics have been accepted widely, more and more research has focused on the pulsatile modulation of RBPs in an attempt to provide better perfusion. In this study, we investigated the effects of an axial RBP serving as the right ventricular assist device on pulmonary hemodynamics and gas exchange using a numerical method with a complete cardiovascular model along with airway mechanics and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…To avoid in vivo experiments, in our study, system simulations using a validated cardiovascular system model coupled with the blood pump model were conducted using the Simulink/MATLAB software to obtain the inlet and outlet pressures of the pump for setting the boundary conditions. The system simulations were proven to replicate similar physiological waveforms when a blood pump was implanted ( Huang et al, 2018 , 2019 ), which is adequate for comparative CFD studies. This provides a convenient and effective means for obtaining the boundary conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid in vivo experiments, in our study, system simulations using a validated cardiovascular system model coupled with the blood pump model were conducted using the Simulink/MATLAB software to obtain the inlet and outlet pressures of the pump for setting the boundary conditions. The system simulations were proven to replicate similar physiological waveforms when a blood pump was implanted ( Huang et al, 2018 , 2019 ), which is adequate for comparative CFD studies. This provides a convenient and effective means for obtaining the boundary conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic and pulmonary venous systems are both characterized simply by lumped resistance and lumped compliance. More details and parameter values could be referred to the reference [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…A complete numerical model of the cardiovascular system from a previous study [11], shown in Fig 2, is adopted in this study to provide a platform for validating the on-line identification algorithm. The cardiovascular model includes both systemic and pulmonary circulation.…”
Section: Cardiovascular Modelmentioning
confidence: 99%
“…The whole numerical model, shown in Figure 2, mainly contains the following four sub-models: a cardiovascular model, which includes both systemic and pulmonary circulatory pathways; an airway mechanics model; an O 2 gas exchange model; and an RBP model. 15 The cardiovascular model interacts with the gas exchange model by time-varied blood flow, while the gas exchange model describes the diffusion of gas from the airway mechanics model across the alveolar–capillary membrane. The connections between the sub-models are clearly shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%